2015
DOI: 10.1111/tpj.13078
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient heritable plant genome engineering using Cas9 orthologues from Streptococcus thermophilus and Staphylococcus aureus

Abstract: SUMMARYThe application of the clustered regularly interspaced short palindromic repeats (CRISPR)/Cas system of Streptococcus pyogenes (SpCas9) is currently revolutionizing genome engineering in plants. However, synthetic plant biology will require more complex manipulations of genomes and transcriptomes. The simultaneous addressing of different specific genomic sites with independent enzyme activities within the same cell is a key to this issue. Such approaches can be achieved by the adaptation of additional b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
191
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 232 publications
(197 citation statements)
references
References 38 publications
3
191
1
2
Order By: Relevance
“…Recently, StCas9 and SaCas9 mediated genome editing was shown in Arabidopsis (Steinert et al, 2015), and SaCas9 mediated genome editing was reported in tobacco and rice (Kaya et al, 2016). These orthogonal Cas9 systems use different Cas9 proteins, PAM requirements and gRNA scaffolds for target recognition, hence expanding the targeting sites defined by the most popular SpCas9 system.…”
Section: Broadening Targeting Ranges With Orthogonal Crispr-cas9 Systemsmentioning
confidence: 99%
“…Recently, StCas9 and SaCas9 mediated genome editing was shown in Arabidopsis (Steinert et al, 2015), and SaCas9 mediated genome editing was reported in tobacco and rice (Kaya et al, 2016). These orthogonal Cas9 systems use different Cas9 proteins, PAM requirements and gRNA scaffolds for target recognition, hence expanding the targeting sites defined by the most popular SpCas9 system.…”
Section: Broadening Targeting Ranges With Orthogonal Crispr-cas9 Systemsmentioning
confidence: 99%
“…Editing plant genomes without introducing foreign DNA into cells may alleviate regulatory concerns related to genetically modified plants. Transformed preassembled complexes of purified Cas9 protein and guide RNA into plant protoplasts of A. thaliana have achieved targeted mutagenesis in regenerated plants at frequencies of up to 46 % with the targeted sites contained germline-transmissible small insertions or deletions (Steinert et al 2015;Woo et al 2015).…”
Section: Arabidopsis Thalianamentioning
confidence: 99%
“…However, SpCas9 variants were initially designed for applications in mammalian cells and have not yet been tested in plants [38]. Regarding SpCas9 orthologs, StCas9 and SaCas9 have recently been used to trigger mutagenesis in A. thaliana with high efficiency and without any cross interference between nucleases and sgRNA from different species [52]. SaCas9 which showed the highest mutation efficiency (90%) seems to be the most promising for CRISPR-induced gene knock-in.…”
Section: Spcas9 Variants and Orthologsmentioning
confidence: 99%